An integrated fuzzy analytic hierarchy process and life cycle optimization model for microalgae production / Tan Jully - Tan, Jully (2018)
Microalgae biofuel have the potential to overcome many of the limitations and present as a newly emerging clean energy that could replace fossil fuels. To produce a sustainable commodity or product, adverse environmental impacts from the overall process cannot be ignored. Development of cost effective processes for microalgae is considered to be the most significant challenge in commercializing microalgae biofuel production. Optimization of sustainable process plant configuration requires the use of systematic assessment methods in assessing on the usage of natural resources, release of pollutants and generation of environmental impact. The challenges in multi-objective optimization (MOO) is in identifying the appropriate aggregation method to integrate the objectives into a single performance index which is typically done by assigning importance weights to the different objectives. Life cycle assessment (LCA) for microalgae had been conducted extensively focused on comparing its environment impacts for microalgae biofuel production. Researches were also been undertaken to identify the feasible use of different methods for microalgae production. However, there is no consensuses on which of these methods are preferable. Novel integrated fuzzy analytic hierarchy process (FAHP) and life cycle optimization (LCO) framework for microalgae production are presented in this thesis. This includes the insight based on LCA studies and the uncertainty in decision making for technologies selection of microalgae production, taken into consideration of MOO technique. FAHP is incorporated into this research to monitor the uncertainty over the decision making process. Three different microalgae cultivation methods (open pond, tubular photobioreactor and flat-plate photobioreactor), four different harvesting methods (sedimentation by flocculation, flotation, centrifugation and filtration) and four different drying methods (sun drying, spray drying, drum drying and freeze drying) are used as case study to illustrate the capability of integrated FAHP-LCO model. These different methods are evaluated under the three selection criteria, i.e.: production capability, economic and environmental concern. They are prioritized using FAHP. Data from the scientific publication and based on theory for material and balance are used in LCA. Commercial optimization software LINGO v14 are used to solve FAHP and LCO equations. The results showed that flat-plate photobioreactor is preferred among others cultivation system when take into the consideration of environment factors (water, energy and carbon footprint) in the MOO. Followed by filtration and sun drying are chosen as best methods for harvesting and drying processes Sensitivity analysis is conducted and provides insights on the robustness of the decision model and enables the understanding of critical criteria that would significantly influence the ranking of the alternatives. The proposed integrated FAHP-LCO approach therefore proven that it can effectively deal with the uncertainty of judgment in the decision making process in the evaluation of microalgae production selection.